1990
DOI: 10.1136/bjsm.24.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a herbal yeast food supplement and long-distance running on immunological parameters.

Abstract: The effect of a food supplement on immunological parameters of 16 long-distance runners was tested in a randomized, double-blind and placebo-controlled trial. The supplement comprised plasmolysed herbal yeast, malt, honey, and orange juice. No statistically significant differences between the two groups regarding the following variables were detected at three sessions at rest and immediately after a 21 km run: total and differential white blood cell counts, numbers of B-and T-cells and Tsubpopulations, concana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The authors Haralmabie (24), Hanson (25) and Weiss (26) As an important serum marker for the activation of the cellular immune system, neopterin was studied more recently by several other investigators (27)(28)(29)(30)(31)(32). Rokos (27) studied four male subjects aged 31 to 47 before, during and after 100 min of jogging.…”
Section: Discussionmentioning
confidence: 99%
“…The authors Haralmabie (24), Hanson (25) and Weiss (26) As an important serum marker for the activation of the cellular immune system, neopterin was studied more recently by several other investigators (27)(28)(29)(30)(31)(32). Rokos (27) studied four male subjects aged 31 to 47 before, during and after 100 min of jogging.…”
Section: Discussionmentioning
confidence: 99%
“…The significant changes in athletes included: (i) lower serum IgA, IgG and IgM levels and a trend towards lower levels of IgG2 subclass; ( [13], where the differences in IgG subclasses were also noted to be small on an absolute scale. Ricken & Kindermann [29] have also shown that low levels of serum immunoglobulins are associated with an increased susceptibility to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of cytokines, such as IL-6 or tumor necrosis factor-␣, are known to be present in the bloodstream after exercise (6,38). IL-2, IL-4, TGF-␤, and IFN-␥, however, are least likely to be induced during or after acute exercise (18,19,27,35). Thus it is reasonable to suppose that these cytokines may not affect CXCR4 expression.…”
Section: ϫ8mentioning
confidence: 99%